Dissecting the Molecular Mechanism of Wang-Bi Capsule in the Treatment of Experimental Rheumatoid Arthritis Based on Synovial Tissue Proteomic Analysis. (18th October 2021) - Shu, Haiyang; Shi, Yingjie; Li, Li; Zhao, Ning; Lu, Cheng; Lu, Aiping; He, Xiaojuan
Abstract : Wang-Bi capsule (WB) is a traditional Chinese medicine formula and has been applied for rheumatoid arthritis (RA) treatment for many years. However, its underlying molecular mechanisms still remain unclear. In this study, collagen-induced arthritis (CIA) rats were used to observe the therapeutic effect of WB used at different time points, and the proteomic analysis of synovial tissue was applied to reveal its basic molecular mechanisms. The results demonstrated that WB not only effectively ameliorated the symptoms and synovitis, but also downregulated the serum levels of inflammatory cytokines/chemokines in CIA rats. Furthermore, the proteomic analysis of synovial tissue showed that WB could regulate several signaling pathways associated with inflammation or cell migration, such as "IL-1 signaling, " "IL-8 signaling, " and "CXCR4 signaling." The expression levels of proteins including matrix metalloproteinase 3 (MMP3), MMP19, lipopolysaccharide-binding protein (LBP), serine/threonine kinase interleukin-1 receptor-associated kinase 4 (IRAK4), and actin-related protein 2/3 complex subunit 5 (ARPC5) in these pathways were downregulated significantly by WB when compared with the model group. In sum, this study indicated that WB had obvious inhibitory effects on synovitis of CIA rats, and the mechanisms of which may be involved in downregulating the expression levels of several key proteins including MMP3, MMP19, LBP, IRAK4, and ARPC5.